Investigation of caliciviruses and astroviruses in Gabonese rodents: A possible influence of national and international trade on the spread of enteric viruses - Mbou-Boutambe, Clark; Mombo, Illich, Manfred; Rougeron, Virginie; Degrugillier, Fanny; Gauthier, Philippe; Makanga, Boris; Ngoubangoye, Barthélémy; Leroy, Eric, M.; Prugnolle, Franck; Boundenga, Larson (Infection, Genetics and Evolution, 2024)
The original contributions presented in the study are included in the article, further inquiries can be directed to the corresponding author. The partial genome/coding sequences of study viruses can be found in the National Center for Biotechnology Information Database/ GenBank under the accession numbers PP516503 to PP516520. Access to the fasta files can be provided upon request. International audience Highlights: • All Rodent were tested negative for caliciviruses. • Rattus rattus is the only species infected by astroviruses. • No rodents were infected with human astroviruses. • Transportation such as land and railway, as well national and international trade, are likely to facilitate spread of enteric viruses by the dissemination of rodents.Abstract: Caliciviruses (Caliciviridae) and astroviruses (Astroviridae) are among the leading cause of non-bacterial foodborne disease and gastroenteritis in human. These non-enveloped RNA viruses infect a wide range of vertebrate species including rodents. Rodents are among the most important hosts of infectious diseases globally and are responsible for over 80 zoonotic pathogens that affect humans. Therefore, screening pathogens in rodents will be is necessary to prevent cross-species transmission to prevent zoonotic outbreaks. In the present study, we screened caliciviruses and astroviruses in order to describe their diversity and whether they harbor strains that can infect humans. RNA was then extracted from intestine samples of 245 rodents and retrotranscribed in cDNA to screen caliciviruses and astroviruses by PCRs. All the samples tested negative for caliciviruses and while astroviruses were detected in 18 (7.3%) samples of Rattus rattus species. Phylogenetic analyses based on the RdRp gene showed that all the sequences belonged to Mamastrovirus genus in which they were genetically related to R. rattus related AstVs previously detected in Gabon or in Rattus spp. AstV from Kenya and Asia. These findings suggested that transportation such as land and railway, as ...